The role of interictal discharges in ictogenesis - A dynamical perspective - Chvojka, Jan; Kudlacek, Jan; Chang, Wei-Chih; Novak, Ondrej; Tomaska, Filip; Otahal, Jakub; Jefferys, John G. R; Jiruska, Premysl (Epilepsy & behavior, 2021)
Interictal epileptiform discharge (IED) is a traditional hallmark of epileptic tissue that is generated by the synchronous activity of a population of neurons. Interictal epileptiform discharges represent a heterogeneous group of pathological activities that differ in shape, duration, spatiotemporal distribution, underlying cellular and network mechanisms, and their relationship to seizure genesis. The exact role of IEDs in epilepsy is still not well understood, and there remains a persistent dichotomy about the impact on IEDs on seizures. Proseizure, antiseizure, and no impact on ictogenesis have all been described in previous studies. In this article, we review the existing knowledge on the role of interictal discharges in seizure genesis, and we discuss how dynamical approaches to ictogenesis can explain the existing dichotomy about the multifaceted role of IEDs in ictogenesis. This article is part of the Special Issue "NEWroscience 2018".
Keywords: elektroencefalografie; Neurons; Electroencephalography; neurony; Seizures; Humans; lidé; epilepsie; Epilepsy; záchvaty